O (nad)używaniu przedrostka „post” w czasach (po)nowoczesnych - Stachewicz, Krzysztof (Wydział Teologiczny, UAM, 2012)
Artykuł podejmuje problem współczesnego nadużywania przedrostka „post” w dyskursie z zakresu nauk społecznych i humanistycznych oraz w języku publicznym i potocznym. Zdaje się, że sytuacja człowieka epoki (po)nowoczesnej jest sytuacją postczłowieka, żyjącego w postrzeczywistości. Opisywane w artykule klimaty nie mogą nie wpływać na rozumienie, ale i przeżywanie rzeczywistości małżeństwa i rodziny. W każdym razie warto przyglądać się implikacjom płynącym z nadreprezentacji prefiksu „post” we współczesnych narracjach.

The article deals with the problem of overusing the prefix “post” in social studies discourse and humanistic discourse as well as in public and colloquial language in contemporary times. The situation of a human being in the (post)modern epoch seems to be the situation of a post-human being living in post-reality. Trends discussed in the article must influence not only the understanding but also the experiencing of the reality of marriage and family. It is certainly worthwhile to analyze the implications arising from an over-representation of the prefix “post” in contemporary narrations.
On (Over)using the Prefix „Post” In (Post)modern Times
Keywords: Ponowoczesność; Postmodernity; Postmodernizm; Postmodernism; Homo videns